Aspectos relevantes na gerência de uma plataforma de perfuração marítima - Oliveira, Irapuan Quadros de (1998)
Nowadays, the word 'ehange' is up-to-date and it turned out to be the new organizational paradigm. Everybody wants to ehange, to transform and to be prepared for the future. Change represents the opportunity for growth, innovation, response to ereativity needs, but, on the other hand, it also leads to fear, eonfliet and tough negotiations. The foeus of this doeument is eoneerned to the managers' roles in off-shore drilling rigs at Petrobras, with some analysis of their praetiees and suggesting attitudes that would be better when faeing new seenarios. This study also includes relevant items of an organizational ehange and the requirements in a restrueturing proeess, in order to allow the development of the employees, the proeedures and the organization as a whole.